Sub-micron-sized hafnium (Hf) cathode with excellent thermal emission performance and superior hardness synthesized by powder metallurgy route. (1st July 2023) - Hao, L.Y.; Shen, S.K.; Liu, X.; Chen, H.Q.; Xie, Z.M.; Yang, Y.F.; Liu, P.; Liu, Y.; Fu, E.G.
Abstract: Here we report a sub-micron-sized hexagonal closest packed (HCP) hafnium (Hf) cathode with excellent thermal emission performance and superior hardness. Its thermal emission current density at the same applied voltage and temperature is about 355–392% of that of the traditional HCP Hf cathode, and its hardness is about 752% of that of the latter. These excellent thermal emission performances originate from the reduction of average work functions caused by the weak preferred orientation effect due to the nanoscale grain, leading to a greater thermal emission current density and cathode lifetime in comparison with face-centered cubic (FCC) Hf conterpart. These findings will provide a promising pathway to make much more efficient air and water vapor plasma torches. Graphical abstract: Image, graphical abstract